DETERMINASI KARAKTERISTIK KOMITE AUDIT DALAM MEMPREDIKSI KONDISI FINANCIAL DISTRESS STUDI EMPIRIS PERUSAHAAN SEKTOR JASA YANG TERDAFTAR DI BEI TAHUN 2010-2012 - Duwi Setiyani (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2014)
Financial distress is a condition where a company cannot meet or has difficulty paying off its financial obligations to its creditors. In financial case, corporate governance parties who had an effect on financial distress is the audit committee. This study investigates the impact audit committee characteristic on financial distress. The audit committee characteristics that use in this study are size of audit committee, independence of audit committee, frequency of audit commitee meeting, competence of audit committee, female audit committee, and audit committee nationality, this study use two control variable is sales growth and KAP reputation. The data being used is from annual report serices company which is listed in BEI in 2010-2012 period. Data collecting method which used in this research is metod purposive sampling. Based on the method purposive sampling, research sample total is 80 companies. Data analysis using logistic regression with SPSS 17. The result show that independence ofaudit committee, frequency of audit commitee meeting, female audit committee, and audit committee nationality has negative affect with financial distress. Size of audit committee and competence of audit committeem has not negative affect with financial distress.